2009
DOI: 10.1523/jneurosci.4726-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Neural Changes after Gains and Losses of Conditioned Reinforcers

Abstract: Human behaviors can be more powerfully influenced by conditioned reinforcers, such as money, than by primary reinforcers. Moreover, people often change their behaviors to avoid monetary losses. However, the effect of removing conditioned reinforcers on choices has not been explored in animals, and the neural mechanisms mediating the behavioral effects of gains and losses are not well understood. To investigate the behavioral and neural effects of gaining and losing a conditioned reinforcer, we trained rhesus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
135
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(150 citation statements)
references
References 68 publications
13
135
1
1
Order By: Relevance
“…Neurons in orbitofrontal and anterior cingulate cortex, and TANs in striatum, respond differentially to aversive airpuffs, reward liquids, and their predictive stimuli and follow reversal between punishment and reward (10,255,452,592). In dorsolateral prefrontal cortex, more neurons respond to reward than airpuff (283) and are differentially activated by gains or losses of reward tokens (532). In medial prefrontal cortex, dorsal neurons respond more frequently to air puffs, whereas ventral neurons are more sensitive to liquid reward (372).…”
Section: Distinction To Unrewarding Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurons in orbitofrontal and anterior cingulate cortex, and TANs in striatum, respond differentially to aversive airpuffs, reward liquids, and their predictive stimuli and follow reversal between punishment and reward (10,255,452,592). In dorsolateral prefrontal cortex, more neurons respond to reward than airpuff (283) and are differentially activated by gains or losses of reward tokens (532). In medial prefrontal cortex, dorsal neurons respond more frequently to air puffs, whereas ventral neurons are more sensitive to liquid reward (372).…”
Section: Distinction To Unrewarding Eventsmentioning
confidence: 99%
“…Neuronal signals reflect the sum of positive and negative values from liquid or food rewards and aversive liquids or air puff punisher in monkey dopamine neurons (FIGURE 11D) (157,160) and anterior cingulate cortex (10), and from odor rewards in human orbitofrontal cortex (190). Compatible with coding negative value as component for Equation 25, some frontal cortical neurons are depressed by losses of gained rewards (532). Ideally, neuronal investigations would test EUsum with all constituent components, although this is impractical and experimenters usually investigate only a few of them at a time.…”
Section: Equation 25mentioning
confidence: 99%
See 1 more Smart Citation
“…dmPFC is likewise activated in fMRI studies of reinforcement learning and action selection (Behrens et al, 2007;Botvinick, 2007;Hare et al, 2011;Vickery et al, 2011;Kolling et al, 2012;Boorman et al, 2013;Economides et al, 2014). Combined with evidence from single-unit recording and lesion studies (Kennerley et al, 2006;Seo and Lee, 2009;Sheth et al, 2012), this has led to the idea that dmPFC subserves a role in learning from outcomes, as well as in deploying learnt values in action selection (Alexander and Brown, 2011;. Despite partially different functional connotations of vmPFC and dmPFC, both areas consistently tend to coactivate in fMRI studies of human decision making (FitzGerald et al, 2009;Hare et al, 2011;Nicolle et al, 2012;Boorman et al, 2013), which has rendered it difficult to understand the relation between these two regions within the decision making network.…”
Section: Time-frequency Analysis Of Dmpfc and Vmpfc Activationmentioning
confidence: 99%
“…Previously, the influence of outcome reward had been shown to affect activity during a learning task (Seo, Barraclough, & Lee, 2007;Seo & Lee, 2009). Histed et al (2009) showed that a given trial's outcome had a direct effect on a trial-to-trial basis and that behaviour was altered solely on the basis of the previous trial's outcome (e.g., Seo, Barraclough, & Lee, 2007;Seo & Lee, 2009).…”
Section: Trial-by-trial Learningmentioning
confidence: 99%